2013
DOI: 10.1111/ajt.12488
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health Status and Quality of Life of Related Versus Paid Unrelated Living Kidney Donors

Abstract: The aim of this cross-sectional study was to assess the health status and quality of life (QOL) of paid unrelated versus related living kidney donors postdonation at Shiraz Transplant Center in Iran. We invited all donors (n ¼ 580, 347 paid unrelated, 233 related) who underwent donor nephrectomy at our center from 2004 to 2010 to participate in a health survey and physical examination. Of 580 donors, 144 consented to participate; participation of paid unrelated donors was significantly lower than related (52/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…There are few limited reports from single centers that describe only 1 or 2 aspects of the consequences of living donation [20,21]. This ignorance may be mainly due to lack of any system for living donation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few limited reports from single centers that describe only 1 or 2 aspects of the consequences of living donation [20,21]. This ignorance may be mainly due to lack of any system for living donation.…”
Section: Discussionmentioning
confidence: 99%
“…Fallahzadeh also showed that the general health of donors and their remaining kidney function in paid unrelated donors are inferior in comparison with related living donors [21].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Living Unrelated kidney donation (LURD). Due to the long-waiting list of patients seeking organ transplant, the Iranian kidney transplant model has been at the center of attention (13). Iran has the shortest waiting list for kidney transplants in the world, while the United States as well as European countries have a very long waiting list (14).…”
Section: Kidney Transplantation In Iran and Other Countriesmentioning
confidence: 99%
“…Additionally, we view such incentives as ethically problematic, because the direct involvement of money (other than reimbursement of donor costs, below) commodifies the human body and creates vulnerability to exploitation. Iran provides a stipend to living kidney donors (approximately $400) and one year of free medical insurance [35]. Controversially, the Iranian government permits the exchange of money between organ recipients and their donor candidates (even providing a "private space" where these negotiations can take place) [36].…”
Section: Policy Optionsmentioning
confidence: 99%